2019
DOI: 10.21203/rs.2.13324/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of F11R in Pancreatic Cancer Malignancy and Its Clinical Implication as a Therapeutic Target

Abstract: Background The F11 receptor belongs to the immunoglobulin superfamily and is expressed in epithelial and endothelial cells. F11R mediates the formation of tight junctions between the epithelium and endothelium, and participates in the invasion and metastasis of tumor cells. We have previously shown that the F11R gene is closely related to KRas (P= 0.76), a known therapeutic target for pancreatic cancer (PCa). In recent years, it has been found that F11R is expressed in different tumors and has biological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Through pre-experiment, we found that the F11R gene was highly expressed in five pancreatic cancer cell lines (MIA paca-2, bxpc-3, cfpac-1, SW1990, and PANC-1) and tumor specimens from 30 pancreatic cancer patients (data not shown). All of our experimental results can also be seen in the preprint (v1_covered.pdf ( https://researchsquare.com ) [ 32 ]. As one of the most commonly used cell models, and considering the expression level of F11R, PANC-1 was used as the model in all our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Through pre-experiment, we found that the F11R gene was highly expressed in five pancreatic cancer cell lines (MIA paca-2, bxpc-3, cfpac-1, SW1990, and PANC-1) and tumor specimens from 30 pancreatic cancer patients (data not shown). All of our experimental results can also be seen in the preprint (v1_covered.pdf ( https://researchsquare.com ) [ 32 ]. As one of the most commonly used cell models, and considering the expression level of F11R, PANC-1 was used as the model in all our experiments.…”
Section: Discussionmentioning
confidence: 99%